Subtraction-free and bisulfite-free specific sequencing of 5-methylcytosine and its oxidized derivatives at base resolution - Yibin Liu (Nature Portfolio, 2021)
Specific and quantitative sequencing of cytosine modifications is challenging at base-resolution. Here the authors present TAPSβ and CAPS for subtraction-free whole genome sequencing of 5mC and 5hmC.